12 Steps benefit drug use clients, but engagement proves challenging. Issue 33 (21st August 2020) - Enos, Gary
Abstract : It may be more difficult to engage individuals with illicit drug use disorders into 12‐Step participation compared with those with alcohol use disorders, but newly published data suggests that the effort carries a significant payoff.